Age-related differences in ventricular remodeling and long-term heart failure outcomes following acute coronary syndrome. (25th November 2020) - Adamson, P.D; Verryt, T; Frampton, C.M; Troughton, R; Doughty, R.N; Richards, A.M
Abstract: Background: Older patients are at increased risk of heart failure hospitalization following acute coronary syndrome (ACS). Purpose: We sought to determine whether this increased hazard was related to differing patterns in left ventricular (LV) remodeling over the first 12 months after ACS. Methods: In a prospective multi-centre observational cohort study, 2, 140 patients with ACS underwent echocardiography at 1, 4, and 12 months following the index event. Long-term heart failure hospitalisation events were captured for a median 4.8 (IQR 3.4–6.5) years and the relative risk compared between individuals ≤65 years and those >65 years using a multivariable Cox model adjusted for baseline clinical (sex, blood pressure, coronary revascularisation) and echocardiographic (LV end diastolic and end systolic volumes, LV ejection fraction, interventricular septal wall thickness, and E/e') variables recorded at baseline and 12 months. Results: The 1177 (55%) participants who were >65 years were more likely to be women (34% versus 22%), had higher blood pressure, were more likely to present with non-ST elevation ACS, demonstrated smaller increases in peak myocardial biomarkers and were less likely to undergo coronary revascularization during the index admission (43.2% versus 72.3%; p<0.001 for all comparisons). At the 1 month visit, after indexing for body surface area, older patients had similar LV end diastolic but larger end systolic volumes (p=0.029), lower LV ejection fractions, and greater left ventricular mass and diastolic filling pressure estimates (E/e' 14 versus 10; p<0.001 for all) compared with the young. Systolic volumes appeared to further diverge at 12 months (p=0.064) however LV mass did not change in either group. In unadjusted analysis older patients were at increased risk of future heart failure hospitalization (HR 4.1, 95% CI 3.2–5.3). This increased risk persisted after adjustment for differences in baseline clinical and echocardiography data, and LV remodeling (adjusted HR 2.4, 95% CI 1.5–3.9). Conclusions: Older patients experience a more eccentric remodeling pattern over the 12 months following ACS. Older individuals remain at increased risk of long-term heart failure hospitalization after accounting for clinical and echocardiographic characteristics. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): New Zealand Heart Foundation, New Zealand Health Research Council